The influence of ferrous ions on the efficiency of aqueous photocatalytic oxidation of 2-ethoxy ethanol - D. Klauson; S. Preis (International Journal of Photoenergy)
The complex influence of ferrous ions on the efficiency of aqueous photocatalytic oxidation (PCO) of 2-ethoxyethanol (2-EE) was examined. A drastic efficiency increase at lower concentrations of ferrous ions was observed to change to a sharp decrease at higher concentrations. An explanation was proposed for the observed phenomena based on the low sensitivity of the pollutant towards radical-oxidation reactions and the competitive adsorption of metallic ions and 2-EE on the TiO2 surface.